2022
DOI: 10.3390/molecules27134284
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Injury Caused by Chronic Alcohol Exposure—A Pilot Study Based on Proteomics

Abstract: Chronic alcohol exposure can cause myocardial degenerative diseases, manifested as cardiac insufficiency, arrhythmia, etc. These are defined as alcoholic cardiomyopathy (ACM). Alcohol-mediated myocardial injury has previously been studied through metabolomics, and it has been proved to be involved in the Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway concerning unsaturated fatty acids biosynthesis and oxidative phosphorylation, which tentatively explored the mechanism of ACM induced by chronic drinking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Many previous studies have shown that lipid metabolism is related to many biological functions, being essential for many biochemical reactions ( 32 ). It has been found that the levels of unsaturated fatty acids (e.g., linoleic acid and arachidonic acid) were significantly down-regulated in a high-fat-induced model group, suggesting enhanced peroxidation and oxidative stress ( 33 ). Analysis of liver tissue sections has confirmed that peroxidation and oxidative stress could decompose apolipoprotein B protein, thereby weakening the secretion of very low-density lipoprotein (VLDL), reducing the output of liver TG and facilitating the accumulation of TG in the liver ( 34 ).…”
Section: Resultsmentioning
confidence: 99%
“…Many previous studies have shown that lipid metabolism is related to many biological functions, being essential for many biochemical reactions ( 32 ). It has been found that the levels of unsaturated fatty acids (e.g., linoleic acid and arachidonic acid) were significantly down-regulated in a high-fat-induced model group, suggesting enhanced peroxidation and oxidative stress ( 33 ). Analysis of liver tissue sections has confirmed that peroxidation and oxidative stress could decompose apolipoprotein B protein, thereby weakening the secretion of very low-density lipoprotein (VLDL), reducing the output of liver TG and facilitating the accumulation of TG in the liver ( 34 ).…”
Section: Resultsmentioning
confidence: 99%
“…Kakimoto et al [86] utilized shotgun proteomics to analyze the mechanism of death in acquired cardiac hypertrophy autopsy, and indicated that the stepwise upregulation of sarcomere protein is a danger signal ACH, which may help to diagnose the sudden cardiac death of ACH. Ma et al [87] selected 56 DEPs with TMT-based LC-MS/MS, and proposed that the chronic ethanol exposure could lead to hypertrophy of cardiomyocytes, and the dilation of the ventricle, etc. Additionally, proteomics also has an obvious advantage in detecting postmortem DEPs for PMI estimation too.…”
Section: Proteomicsmentioning
confidence: 99%